Evaluation of partial thickness suturing technique for the repair of aural haematoma in dogs - Asha Latha A (Department of Veterinary Surgery and Radiology, College of Veterinary and Animal Sciences, 2004)
The study was carried out in twelve selected clinical cases of aural haematoma in dogs of different breeds of either sex presented to the College Veterinary Hospitals at Mannuthy and Kokkalai. The animals were divided into two groups viz., Group I and Group II, each consisting of six animals. In Group I, surgical drainage was carried out and the dead space was obliterated by applying a series of through and through (full thickness) interrupted mattness suture. In Group Il, surgical drainage was carried out and the dead space was obliterated by applying a series of partial thickness interrupted mattress suture. In Group I, the dogs were aged three to eight years and the duration of illness varied from three to fourteen days. Shaking of the head, scratching and drooping of the affected pinna were observed in all the dogs, except scratching in one dog. Length of the ear and haematoma varied from 7.4 cm to 13.7 cm and 7 cm to 12 cm respectively. Width of ear and haematoma varied from 4.7 cm to 9.2 cm and 3.6 cm to 7.4 cm respectively. Thickness of haematoma varied from 2.1 cm to 5.5 cm. The physiological parameters like rectal temperature, pulse rate and respiratory rate was found to be within normal range. The haematological values such as, packed cell volume, total erythrocyte count, haemoglobin concentration, total leucocyte count and differential leucocyte count were also within normal physiological range. Post-operatively self mutilation of wound, scratching and shaking of the head were reported in a few animals and carriage of affected ear was drooped in all the animals. There was no accumulation of blood or exudates in any of the animals. Most of the animals retained bandage. Photographs of the affected ear was taken before surgery, immediately after operation and thereafter on third, sixth, ninth and thirtieth day and were observed for evaluating the post-operative cosmetic appearance of the